(untitled) (Fiep Bulletin - online, 2014)
This paper presents the results of quantitative research focused on leisure and sports activities among a specific target group – caravanners. These people pursue their caravanning activities in their free time and this activity represents a significant and important part of their lifestyle. Caravanning is a reemerging form of leisure activity which is becoming increasingly more fashionable as recent history has seen a general improvement in the standard of living, making such a choice possible. This form of motor tourism can be examined from the perspective of the issue of sports tourism, as well as an integral element of lifestyle. This paper evaluates the preferred types physical activities pursued by this group of respondents, and examines their preferred destination and season. It also includes an assessment of the general profile of the Czech caravanners from the perspective of the fundamental characteristics of their socio-economic and demographic features. The last part of the paper is devoted caravanning events - their frequency, types, locations and the ways in which they are organized.